Comparison of multistranded wire and fiber-reinforced composite retainers effects on periodontium: A randomized clinical trial - Nasreen Iqbal NAGANI; Imtiaz AHMED (Dental Press Editora, 2023)
ABSTRACT Introduction: Fixed orthodontic retainers are very important for treatment stability; however, adverse effects on the health of periodontium can be caused as a result of deposition of plaque and calculus. Objectives: To compare and determine the effects of two mandibular fixed lingual retainers on the periodontal status, and to test the null hypothesis that there would be no significant difference on the periodontium health between the patients using fiber-reinforced composite (FRC) or multistranded wire (MSW) fixed retainers. Methods: A total of 60 subjects were recruited, out of which 6 were excluded and 2 dropped out during the study. Hence, 52 subjects with mean age of 21.5 ± 3.6 years were included in the study. The sample was composed by 8 males (15.4%) and 44 females (84.6%). The participants were randomly divided into two groups: Group 1 received fiber-reinforced composite retainer, while Group 2 received multistranded wire retainer. After insertion, plaque index, calculus index, gingival index and bleeding on probing were compared, after three months (T1), six months (T2), nine months (T3) and twelve months (T4), using Mann-Whitney test with p-value ≤ 0.05 as significant. Results: It could be seen that the health of periodontium deteriorated with the passage of time from T1 to T4 in both group of retainers. However, no statistically significant differences were found between the two groups (p> 0.05). Conclusion: The results of the study indicate that there was no significant difference on the health of periodontium between the patients with FRC and MSW fixed retainers, hence, the null hypothesis was accepted.